2020
DOI: 10.1182/bloodadvances.2019000919
|View full text |Cite
|
Sign up to set email alerts
|

Gilteritinib is a clinically active FLT3 inhibitor with broad activity against FLT3 kinase domain mutations

Abstract: Key Points• Gilteritinib is active against a wide range of clinically relevant activating FLT3 mutations.• Resistance-conferring FLT3 kinase domain mutations are responsible for a minority of clinical resistance to gilteritinib.Gilteritinib is the first FMS-like tyrosine kinase 3 (FLT3) tyrosine kinase inhibitor (TKI) approved as monotherapy in acute myeloid leukemia with FLT3 internal tandem duplication and D835/I836 tyrosine kinase domain (TKD) mutations. Sequencing studies in patients have uncovered less co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 39 publications
2
55
0
Order By: Relevance
“…Similarly, in a study of 18 patients treated with crenolanib, pre- and post-treatment sequencing identified small populations of four NC mutations at baseline which were eliminated over the course of treatment (A833S, D839Y/G, N841K, Y842C) ( 64 ). In a recent in vitro study, gilteritinib was active against multiple NC mutations, including mutations like N676, which are associated with resistance to midostaurin and quizartinib ( 149 ). Finally, in a recent case series, two patients with non- FLT3- ITD or D835 AML were found to have JM FLT3-V592G and KD FLT3-N676K mutations, both of which clinically responded to sorafenib ( 146 ).…”
Section: Ongoing Questions and Controversiesmentioning
confidence: 99%
“…Similarly, in a study of 18 patients treated with crenolanib, pre- and post-treatment sequencing identified small populations of four NC mutations at baseline which were eliminated over the course of treatment (A833S, D839Y/G, N841K, Y842C) ( 64 ). In a recent in vitro study, gilteritinib was active against multiple NC mutations, including mutations like N676, which are associated with resistance to midostaurin and quizartinib ( 149 ). Finally, in a recent case series, two patients with non- FLT3- ITD or D835 AML were found to have JM FLT3-V592G and KD FLT3-N676K mutations, both of which clinically responded to sorafenib ( 146 ).…”
Section: Ongoing Questions and Controversiesmentioning
confidence: 99%
“…D. FLT3 activity is sustained with mutations in N701K and F691L. Ba/F3 cells harboring FLT3 ITD , FLT3 ITD+F701K , and FLT3 ITD+F691L were treated with gilteritinib (0 – 400 nM) for 90 minutes and lysed for immunoblot analysis 4, 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Another set of mutations in the tyrosine kinase domain (TKD) of FLT3 occur in 5-10% of AML patients. In contrast to FLT3-ITD, FLT3 TKD mutations result in less activation of FLT3 and do not increase the risk of relapse 3 [4][5][6] . These mutations occur frequently at the activation loop residue D835 and less commonly at F691 which represents the "gatekeeper" position in FLT3 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data suggest that higher doses of gilteritinib above 200 mg/day may potentially overcome resistance associated with FLT3-F691L mutations. 56 It is important to note that doses of 200–300 were tolerated in the phase I/II trial; however, a dose of 120 mg/day was assessed in the randomized phase III trial and is currently the FDA approved dose.…”
Section: Mechanism Of Resistancementioning
confidence: 99%